Gejala Proliferasi Dinasti Politik di Banten Era Kepemimpinan Gubernur Ratu Atut Chosiyah - Sutisna, Agus (Jurnal Politik Indonesia: Indonesian Political Science Review, 2017)
Since forming into independent provinces, apart from West Java, Banten political life was marked by the strengthening of a political dynasty, both at the provincial and district and city. At the provincial level, the dominance of the local strongmen, Tb. Chasan Sochib in political of Banten is very prominent and managed to put his son, Ratu Atut Chosiyah the governorship for almost two periods (2006-2011 and 2011-2014). Post successes in occupying the post of governor, hypothetically Ratu Atut successfully builds and develop a political dynasty to the various arenas of public life. This research was carried out on the object of governance and practices of government power governor of Banten province, with the aim to identify and explain how political dynasties role this province or political kinship in Banten province in the era of the leadership of Governor Ratu Atut Chosiyah proliferate (distribution, diasporic) in various arenas of public life. This study used a qualitative approach, the method of collecting data and information through interviews, triangulation, literature and documents. The results showed that the role of political dynasties in the era of the l Governor Ratu Atut Chosiyah in Banten show any symptoms of the spread (proliferation, diasporic), not only in the realm of executive and legislative power, but also spread in many arenas of life of society, such as the arena business life, socio-cultural, educational, and organizational.